ORGANIZATIONAL COMMITMENT AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Syardiansah Syardiansah; Riny Chandra; Eva Yuana Lestari (NIAGAWAN, 2024)
Performance is the result of work achieved by an individual or an employee in quality and quantity in accordance with the duties and responsibilities with certain standards where the individual works. Organizational commitment is a belief that an employee has towards the company where the individual works. And job satisfaction is an attitude or feeling that shows how a person's response to his work. This study aims to determine the effect of organizational commitment and job satisfaction on employee performance. The sample in this study totaled 169 employees of PT. Perkebunan Nusantara I Langsa. The research method contained in this research is quantitative research. From the results of the study it was found that partially organizational commitment has a positive and significant influence on employee performance. Job satisfaction has a positive and significant influence on employee performance. And simultaneously organizational commitment and job satisfaction have a positive and significant impact on employee performance. Based on the test results of the coefficient of determination, it was found that organizational commitment and job satisfaction can affect employee performance by 83.1%.